2022
DOI: 10.1021/acs.cgd.1c01330
|View full text |Cite
|
Sign up to set email alerts
|

Order–Disorder Phase Transition between High- and Low-Z′ Crystal Structures of the P1 Space Group

Abstract: We report a crystal structure of Boc-L-methionyl glycine methyl ester (MGP) with eight molecules in the asymmetric unit (Z′ = 8), which is the highest number in dipeptide compounds. Interestingly, its order−disorder phase transition to the crystal structure of Z′ = 4 was observed at −113 °C. The reversible order−disorder character of the phase transition was revealed by single-crystal X-ray diffraction and temperature-dependent second harmonic generation (SHG) signal measurements. The disorder of the methionin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…This may be an interesting development to address this topic further. 63 In conclusion, we re-examined the crystal structure of spironolactone II, finding a temperature-induced order− disorder transition that occurs below 155 K into a monoclinic Z′ = 2 structure, which is related to the three dynamic disorder sites in the molecule. This is particularly interesting, as this disorder is also partially applicable in the room temperature model, thus improving the accuracy of this model that is still being used in modern studies.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…This may be an interesting development to address this topic further. 63 In conclusion, we re-examined the crystal structure of spironolactone II, finding a temperature-induced order− disorder transition that occurs below 155 K into a monoclinic Z′ = 2 structure, which is related to the three dynamic disorder sites in the molecule. This is particularly interesting, as this disorder is also partially applicable in the room temperature model, thus improving the accuracy of this model that is still being used in modern studies.…”
Section: Discussionmentioning
confidence: 90%
“…This theme is also discussed in recent studies exploring polymorphic structures with variable Z ′ and exclusively weak disperse interactions, or more diverse interaction including hydrogen bonds and π-stacking, even including thermal phase transition, albeit irreversible, comparable to our observation in spironolactone II . Another study that explored the order–disorder phase transition with changing Z ′ in space group P 1 used, in addition to single-crystal data, temperature-dependent second harmonic generation signal measurements to better characterize this transition. This may be an interesting development to address this topic further …”
Section: Discussionmentioning
confidence: 99%
“…This change can be clearly observed by XRD, but no signal is present in DSC. TR-SHG does show a different decrease in signal intensity between the two polymorphs 71 . Although the transition can be classified as and order-disorder transition, it is not clear whether it is a first or second order transition in terms of the Ehrenfest classification 72,73 .…”
Section: Mechanistic Studiesmentioning
confidence: 80%
“…A reason for our selection of N , C -protected dipeptides is that the intermolecular interactions of 1–3 are expected to be weaker than that of a typical unprotected dipeptide 15 because both the N - and C -termini are protected so that the amino and carboxy groups are absent. In this context, we recently reported that analogous dipeptide crystals of Boc- l -methionyl- l -glycine methyl ester 16 exhibited temperature-dependent disorder–order phase transition from the crystal structure with eight molecules in the asymmetric unit ( Z ′ = 8) to that of Z ′ = 4 at a very low temperature of −113 °C owing to its weak intermolecular interactions as well as molecular flexibility.…”
Section: Introductionmentioning
confidence: 99%